“As Regarding Rhythm”: Rhythm in Modern Poetry and Cinema - Keller, Sarah (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2010)
This essay examines the connection between modern poetry and cinema through their mutual emphasis on rhythm. It argues that rhythm provides both an alternative mode for structuring non-narrative cinemas as well as an explanatory device for how filmmakers in the modernist milieu believe the cinema works.